2013
DOI: 10.9734/ejnfs/2013/7007
|View full text |Cite
|
Sign up to set email alerts
|

Benefit-Risk Analysis for Foods (BRAFO)- Executive Project Summary

Abstract: This study has been carried out with partial financial support by the Commission of the European Communities, and was coordinated by ILSI Europe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…Results from this research may aid further qualitative and quantitative risk–benefit assessments of coffee consumption, using published approaches (Hoekstra and others ; Verhagen and others ; Boobis and others ; Vidry and others ; Hart and others ) and further activities emphasizing the potential benefits should be pursued. As such, the potential benefits for public health of consuming coffee or not consuming coffee could be calculated for the most convincing benefits (for example, type 2 diabetes and neurological and/or hepatic disorders).…”
Section: Future Workmentioning
confidence: 89%
“…Results from this research may aid further qualitative and quantitative risk–benefit assessments of coffee consumption, using published approaches (Hoekstra and others ; Verhagen and others ; Boobis and others ; Vidry and others ; Hart and others ) and further activities emphasizing the potential benefits should be pursued. As such, the potential benefits for public health of consuming coffee or not consuming coffee could be calculated for the most convincing benefits (for example, type 2 diabetes and neurological and/or hepatic disorders).…”
Section: Future Workmentioning
confidence: 89%
“…The interplay between HBGVs from the perspective of toxicological risk assessment and from the perspective of nutrition have been considered before in many papers, such as, but not limited to, Renwick et al (2004), Verkaik-Kloosterman et al (2012), Bruins et al (2015; EFSA, 2006;NASEM (2018). Moreover, HBGVs for micronutrients have been the underlying considerations for integrated risk-benefit assessment for food and nutrition (Tijhuis et al, 2012a(Tijhuis et al, , 2012bBoobis et al, 2013;Vidry et al, 2013). A detailed review of the different approaches proposed is outside the scope of this Statement.…”
Section: Interpretation Of the Terms Of Referencementioning
confidence: 99%
“…(2015); EFSA, 2006; NASEM (2018). Moreover, HBGVs for micronutrients have been the underlying considerations for integrated risk‐benefit assessment for food and nutrition (Tijhuis et al., 2012a, 2012b; Boobis et al., 2013; Vidry et al., 2013). A detailed review of the different approaches proposed is outside the scope of this Statement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Devos et al., ; Url, ). As discussions become framed more broadly, a more holistic approach to assessing and addressing risks has been suggested, where risks are weighed against benefits (Tijhuis et al., ; Boobis et al., ; Vidry et al., ; Boué et al., ). It has also been suggested that decisions should be made about the acceptability of new technologies in the context of other risks as well as the costs of not using these technologies (Tait and Barker, ).…”
Section: Fit‐for‐purpose Food Safety Risk Assessmentmentioning
confidence: 99%